2011
DOI: 10.1590/s1806-37132011000200011
|View full text |Cite
|
Sign up to set email alerts
|

Biópsia aspirativa transtorácica por agulha fina guiada por TC de lesões pulmonares: resultados e complicações

Abstract: Objective: To analyze the cytological findings of CT-guided percutaneous fine-needle aspiration biopsies of the lung, to demonstrate the diagnostic feasibility of the method in the investigation of pulmonary lesions, and to determine the complications of the procedure, evaluating its safety. Methods: A retrospective analysis of 89 patients with various types of pulmonary lesions who underwent 97 procedures over a period of five years. The patients were divided into groups regarding the indication for the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“… 34 Some groups have also developed expertise in CT-guided transthoracic fine-needle aspiration, showing high diagnostic yield, accuracy, and safety. 35 After 2010, endobronchial ultrasound was introduced in a few large institutions, and the initial experience with 50 cases has been reported. 36 , 37 In most cases, endobronchial ultrasound was recommended for diagnostic purposes (76%), yielding adequate specimens in 74% of the cases.…”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“… 34 Some groups have also developed expertise in CT-guided transthoracic fine-needle aspiration, showing high diagnostic yield, accuracy, and safety. 35 After 2010, endobronchial ultrasound was introduced in a few large institutions, and the initial experience with 50 cases has been reported. 36 , 37 In most cases, endobronchial ultrasound was recommended for diagnostic purposes (76%), yielding adequate specimens in 74% of the cases.…”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“…With regard to other pathology findings, the malignancy rate was the highest for specific malignancy (99.8%, 95% CI, 99.7–99.9%; I 2 = 0.00; 11,884 biopsies in 114 studies) 3,4,69,11–23,2568,70,72–76,78,79,8186,88,90–93,96,99101,103105,108,113–115,118–120,124,126130,132,134,138147 , followed by atypical cells (91.1%, 95% CI, 87.8–94.5%; I 2 = 0.23; 312 biopsies in 41 studies) 4,9,13,14,1720,26,27,29,30,34,37,41,42,46,47,53,64,66,70,74–76,79,85,86,8991,98,101,104,108,115,120,126,129,144,147 , AAH (88.9%, 95% CI, 76.7–100.0%; I 2 = 0.31; 18 biopsies in 6 studies) 8,76,84,126,128,138 , non-specific benign results (20.6%, 95% CI, 17.8–23.4%; I 2 = 0.96; 2574 biopsies in 64 studies) 4,6,8,11,12,19,22,23,26–28,…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have demonstrated that clinical, radiological, and procedural factors are related to the risks of complications (18-20). Yeow et al (21) reported a higher rate of pneumothorax in lesions <2 cm and deeper than 0.1-2 cm and for procedures performed by less-experienced radiologists.…”
Section: Discussionmentioning
confidence: 99%